EU-CELAC Strategic Partnership: Fostering Peace, Democracy, and Human Rights Towards the 2030 UN Sustainable Development Goals - Moure Pino, Ana María; Janas, Witold (Latin American Journal of Trade Policy, 2024)
The Community of Latin American and Caribbean States (CELAC, and the European Union (EU) cooperate in multiple initiatives related to sustainability in Latin America. Joint initiatives undertaken within this partnership strengthen the region’s political dialogue and social and cultural integration in line with the 2030 Agenda for Sustainable Development to eradicate poverty and achieve sustainable development goals.